Perancangan Kampung Tematik Sawah dan Burung Hantu Menjadi Kawasan Wisata - Pratama, Raka Andika; Pangaribuan, Marcellino Sinar Hutama; Basuki, Yudi (Jurnal Riptek, 2022)
The Thematic village is one of the flagship programs, which is a priority program for the Semarang City government. The existence of thematic villages is one of the tourist destinations in Semarang. The development of thematic villages to become tourist destinations is in line with one of the visions and missions of the development of the City of Semarang in 2021â€“2026. In addition, the development of thematic village areas is a form of adaptation by the Semarang City government to revive the tourism sector, which has been on hiatus due to the COVID-19 pandemic. One of the objectives of the development of thematic villages is to increase the potential of a competitive local economy and stimulate industrial development based on research and innovation based on the principles of Pancasila economic democracy. The mission was then followed up by organizing a priority program, namely "Local Economic Empowerment", with priority activities in the form of "Productive Thematic Villagesâ€. One of the areas that was developed into a thematic village is â€œKampung Tematik Sawah dan Burung Hantuâ€. â€œKampung Tematik Sawah dan Burung Hantuâ€ is located in Tambangan Village, Mijen District. This thematic village previously had several tourist attractions, such as photo spots, beautiful views of rice fields, the presence of an owl that was released, and the culinary of Soto Rice. However, all tourism activities in this thematic village have stopped completely due to the COVID-19 pandemic. Therefore, the purpose of this research is to revive tourism activities in this thematic village. The analysis stage begins with collecting data such as infrastructure, social, and economic data for the community, as well as the theory of tourist destinations and best practices that will be used. The next stage is the analysis process of the data that has been obtained and juxtaposed with the theory that has been determined through potential and problem analysis, issue analysis, and GAP analysis. After doing the analysis, the design concept that is suitable for the development of the â€œKampung Sawah dan Burung Hantuâ€ is obtained, namely "Agrotourism based on local potentialâ€. Based on the results of the analysis of the potential, problems, and concepts developed, recommendations for development are obtained, which are divided into three aspects, namely infrastructure, economic, and social aspects.